Two processes in object colour perception - Stanikūnas, Rytis; Vaitkevičius, Henrikas; Švegžda, Algimantas; Viliūnas, Vilius; Daugirdienė, Aušra; Kulikowski, Janus J.; Murray, Ian J. (Psichologija, 2004)
Perception of colour depends on the spectral composition of light that reaches retina and depends as well on various mechanisms of visual system that processes information flow. The few important mechanisms can be distinguished in colour perception: colour adaptation, colour constancy and colour contrast. If the visual field has only one coloured object, then colour perception will be determined by spectral composition of the light and colour adaptation. Whereas mechanisms of colour constancy and colour contrast switches on when in the visual field there are at least two colour objects. Von Kries (1905) have attributed colour constancy phenomenon to theory of receptoral adaptation. But this is theory is applicable to local processes happening in relatively small size of visual field. Craven and Foster (1992) shows that receptor excitation ratios remains constant during change of illumination. But again remains unexplained colour change during adaptation. So, the hypothesis is raised that two processes attribute colour perception: local colour contrast calculation and global adaptation to the background. Therefore the experiments have been carried out to establish the colour contrast and background adaptation impact on colour perception. Four subjects with normal colour vision participated in the experiments. 40 Munsell samples (value 7 and chroma 4) illuminated with one reference illuminant (standard C) and 6 test illuminants (standard A, standard S, cardinal red, cardinal green, cardinal yellow and cardinal blue) were simulated on computer monitor. The dark-adapted subjects have been shown colour samples on neutral background illuminated with one of test illuminants. The task was to match the colour stimuli appearance under reference illuminant. The sequential asymmetric matching procedure was carried out. First subject adapts to neutral background under illuminan C then test stimulus and test background appears for limited time followed by readaptation to neutral background. Then subject is asked to adjust the colour mach under illuminant C. Two different experiment paradigms have been used. In the first one the stimulus had 2° on neutral background covering 20° of visual field. In the second paradigm the stimulus size was the same but the background was covering the all visual field. The adaptation and presentation timings were 1, 5, 30 or 60 seconds. Results under the first experiment paradigm show partial colour constancy for all subjects and for all test illuminants under various adaptation times. Despite quite a long adaptation time of 30 seconds subjects was unable to achieve full colour constancy. Colour constancy improves under second experiment paradigm. 60-second adaptation time is enough to achieve full colour constancy. The less adaptation time (1 or 30 second) gives partial colour constancy. The subject sees two colours (stimulus and background) during the experiment. The colour perception of stimulus and background changes during adaptation time. In the first 5 seconds of adaptation 40–60% of full adaptation level is reached (Fairchild and Reniff, 1995; Werner et al., 2000). Wesner and Shevell (1992, 1994) shown that signals from all visual field have influence on colour perception of object. The first part of our experiment shows that neutral background of 20° gives partial adaptation to background colour. Therefore, increase background illumination to full visual field gives full adaptation to background. So, subject perceives different coloured background under various illuminants as the same neutral (grey) background. We can state that two different systems have been distinguished in the process of colour perception. One system evaluates the colour difference between the stimulus and the background. Second system evaluates the colour of the background. Perceived colour difference during adaptation does not change much, but perceived colour of the background changes a lot and drifts towards neutral colour. The hypothesis of two level colour perception is supported by experimental data.